Air bubbling for membrane fouling control in a submerged direct forward osmosis system for municipal wastewater treatment. Issue 4 (8th February 2019) - Sun, Yan; Gao, Shanshan; Tian, Jiayu; Hao, Xiujuan; Liu, Zhiquan; Shi, Wenxin; Cui, Fuyi
Abstract : Air bubbling along the membrane improves water flux, alleviates the deposition of foulants and inhibits the formation of a fouling layer. Abstract : In this work, the feasibility of air bubbling for membrane fouling control in a submerged direct forward osmosis system for treating municipal wastewater was systematically evaluated. The effect of the air flow rate was first investigated and 3.0 m 3 m −2 h −1 was identified as the optimum value in the experiments. After 52 days of operation, a significantly improved water flux performance was exhibited under air bubbling conditions. In the absence of air bubbling, a dense fouling layer formed on the surface of the membrane which contained large amounts of bacteria, organic matter and inorganics. However, when air bubbling was employed, substantially reduced accumulation of foulants on the surface of the membrane was achieved. The results indicated that air bubbling underneath the membrane could alleviate the deposition of foulants and inhibit the formation and development of a fouling layer on the surface of the membrane effectively. Therefore, air bubbling could be considered as a simple and effective method for alleviating membrane fouling in a submerged direct forward osmosis system.